Bank management : problems and challenges in Nigeria - Ituwe, C.E. (Yola, Nigeria Upper Benue River Basin Development Authority, 1984)
This book provides a practiced oriented study of credit analysis and management, bank operating ratios, management of bank profit and liquidity, bank corporate planning, high incidence of bad debts in Nigerian banks, problems that have either retarded progress of banks or marred their success, not only in Nigeria but also, significantly, in many Third World countries.
Includes bibliographical references.
osc 08/06/2017
Loans
Keywords: Bank Management